Pengaruh Kecerdasan Emosional, Kecerdasan Intelektual dan Komunikasi Kerja Terhadap Kinerja Pegawai Pada KPU Kabupaten Probolinggo - Syafii, Ahmad; Hudzafidah, Khusnik; Rahajeng, Yekti (Universitas Panca Marga, 2024)
This research was conducted at the Probolinggo Regency KPU with the aim of finding out the influence of emotional intelligence, intellectual intelligence and work communication on employee performance at the Probolinggo Regency KPU. The type of research used is quantitative research with a causal relationship approach. In this study the number of samples used was 33 respondents. The sampling technique used is saturated sampling. In proving and analyzing this, validity and reliability tests, classical assumption tests, R2 determination analysis, multiple linear regression tests and hypothesis testing are used. The test results show that: 1) there is an influence of emotional intelligence on employee performance at the Probolinggo Regency KPU. 2) there is an influence of intellectual intelligence on employee performance at the Probolinggo Regency KPU. 3). There is an influence of work communication on employee performance at the Probolinggo Regency KPU.